Using classical reception to develop students' engagement with classical literature in translation. Issue 39 (2019) - Forde, Shane
Abstract : While observing A-level students at my PP2 school, I noticed that their responses to classical texts largely consisted of the identification of stylistic tropes. The students could identify a text's stylistic features but they struggled to articulate and develop their own personal reactions to the text. They had been well-trained in this sort of 'feature-spotting' and therefore their reading experience was narrowly mechanical rather than genuinely exploratory. Every passage they encountered was put through the same analytical process with the unsurprising result that every classical author ended up sounding much the same. This seemed to me to be fundamentally passive way of engaging with literature. I was struck by Muir's contention that 'the pupil should not be a passive recipient in the study of literature' (!974, p.515). Hence, I wanted to devise a teaching strategy that would enable my students to be more active in the formulation of a personal response to the text.